Longitudinal Modifications of the Ozurdex Intravitreal Implant as Imaged by SD-OCT. Issue 3 (May 2015) - Barteselli, Giulio; Dell'Arti, Laura; Pinna, Valentina; Ratiglia, Roberto; Viola, Francesco
Purpose: To describe in vivo longitudinal modifications of the Ozurdex intravitreal implant using spectral-domain optical coherence tomography (SD-OCT) over a 6-month period in an eye treated for retinal vein occlusion (RVO). Methods: Case report. Results: An 82-year-old woman with severe macular edema secondary to branch RVO received an Ozurdex intravitreal implant in the left eye. At day 1, SD-OCT showed that the implant was completely filled with highly reflective dexamethasone. At day 30, complete resolution of macular edema on SD-OCT was noted. At day 60, macular edema started to relapse; SD-OCT scans over the implant showed highly reflective borders that appeared irregular and focally retracted, while the majority of the internal drug had been washed out. At day 180, macular edema returned to baseline levels; SD-OCT scans over the implant showed that the device was contracted with almost complete absence of the internal lumen and drug. Conclusions: Using SD-OCT, we demonstrated that 60 days postinjection most dexamethasone had been released from the Ozurdex implant, which showed multiple irregularities. This was associated with recurrence of macular edema that became worse after 180 days, when there was no residual dexamethasone remaining in the shrunken implant. Low steady levels of the drug in the vitreous and lower biological activity in the retina after the 2-month high-dose release phase may explain why a large number of patients lose clinical improvement 60 days postinjection, as shown by pivotal clinical trials.